Group-1 grass pollen allergens with near-identical sequences identified in species of subtropical grasses commonly found in southeast Asia - Sirirat Aud-In (2020)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Background and objectives: Group-1 grass allergens or beta-expansins (EXPBs) are major allergens from pollen of all grass species. Previous studies showed that they are highly conserved (64-85%) in Pooideae species, which are found mostly in the temperate regions. However, the information about group-1 allergens from common grass species in subtropical areas is still lacking. This study aimed to assess the sequence diversity of group-1 grass pollen allergens in subtropical areas, especially in Southeast Asia. Materials and Methods: Group-1 allergens were cloned from pollen of eight grass species using a single set of primers. Sequences were analyzed and IgE and IgG4 binding regions were compared to the previously reported epitopes in homologous EXPBs. The phylogenetic analysis was used to assess the relationship between sequences of these species and previously characterized EXPBs. Moreover, three-dimensional structure of the EXPB was modeled based on homology to Zea m 1. Results: Sequences from eight grass species were nearly identical. It is conceivable that the primers used for cDNA amplification detected the same isoform in different species. In fact, the deduced amino acid sequences shared 97.79-100% identity with each other and 15/819 polymorphic nucleotide positions were identified. The predicted structure showed that the IgE and IgG4 epitopes and polymorphic residues were located in both domains 1 and 2. The dendrogram presents clustering of class A EXPBs into four groups corresponding to the grass subfamilies. Conclusions: This study identified the allergens with near-identical sequences from different grass species. This isoform could be the major cross-reacting allergenic protein from commonly found grass species.